Methods for Using Tracking Trees to Determine an Ant's Path on a Cartesian Plane via Breadth-First Search - Khairul; Andriani, Tuti; Mentari, Risca Sri (Bahasa Indonesia, 2023)
Because scientific knowledge is expanding at such a dizzying rate, it is essential that society keeps up with technological trends. It is clear from the evolution of this technology that the utilisation of computers as a means to facilitate work and enhance efficiency and effectiveness is also on the rise. Here we see an issue with Artificial Intelligence (AI), a subfield of computer science concerned with teaching computers to mimic human intelligence. When first developed, computers were mostly used for calculations. But computers are becoming more and more integral to human existence. Computers are now expected to be capable of performing any task that a human being can. Their original purpose has expanded beyond simple calculation. Because of our vast store of information and vast experience, we are capable of fixing any problem that arises. One gets more knowledgeable as one learns. An individual's problem-solving abilities are directly proportional to their level of knowledge. The ability to reason, to derive conclusions from one's own knowledge and experience, is an essential complement to one's level of knowledge